A Systematic Review of Educational Robotics in Early Childhood Education from the Workshop on Robotics in Education - Lima, Ana Emanuele Vieira; Sousa, Ihosana De Assis; Garcia, Luciane Terra Dos Santos; Teixeira, Leonardo Rodrigues De Lima; Maia, Cláudia Juliette Do N. Araújo; Gonçalves, Luiz Marcos Garcia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This article aims to analyze the works published in the Workshop on Robotics in Education (WRE), with a focus on the application of Educational Robotics to the first level of basic education. For deepening our understanding of this topic, we carried out an in-depth analysis on 16 relevant studies that we found from this event, which is the most relevant scientific event in South America, covering a period from 2010 to the present day. This comprises the whole WRE existence. Our analysis revealed a rich diversity of teaching methodologies, focusing on different age groups and learning objectives.